The sharia on non-muslims: should they follow? - Hasna Azmi Fadhilah; Fitri Mahara (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Since 2001, the Aceh provincial administration and legislative council have approved the Qanun Jinayat (behavior-governing bylaw) that obliges public in Aceh to follow sharia, the Islamic legal code. While it has been widely accepted by Aceh Muslims, the sharia implementation on non-muslim has sparked a huge debate. To understand the public opinion on this issue, we conducted face-to-face interviews and surveyed more than two hundreds fifty people in Aceh Tengah about their views following the case of Buddhists who were caned for violating sharia law. From the research that we did, our findings reveal that Acehnese people have different opinion on this. A half our respondents, including the non-Muslims do not see sharia law as a burden for them to live in Aceh. While the others, such as human rights activists and non-governmental organizations reported that this law enactment has prompted human rights abuses. Looking at the divisive views, the national and Aceh government are suggested to take further action to avoid more confusion among Acehnese people and religious conflict in the future. Keywords: Sharia Law, Aceh, Non-MuslimsSejak tahun 2001, pemerintah provinsi dan dewan legislatif Aceh telah menyetujui pemberlakuan Qanun Jinayat (peraturan perundang-undangan) yang mewajibkan masyarakat di Aceh untuk mengikuti syariah, kode hukum Islam. Meskipun telah diterima secara luas oleh Muslim Aceh, implementasi syariah bagi non-Muslim telah memicu perdebatan besar. Untuk memahami opini publik mengenai masalah ini, kami melakukan wawancara tatap muka dan mensurvei lebih dari dua ratus lima puluh orang di Aceh Tengah mengenai pandangan mereka menyusul kasus seorang penganut Buddha yang dicambuk karena melanggar hukum syariah. Dari penelitian yang kami lakukan, temuan kami mengungkapkan bahwa orang Aceh memiliki pendapat yang berbeda-beda mengenai hal ini. Setengah responden kami, termasuk non-Muslim, tidak melihat hukum syariah sebagai beban bagi mereka untuk tinggal di Aceh. Sementara yang lainnya, seperti aktivis Hak Asasi Manusia dan Lembaga Swadaya Masyarakat melaporkan bahwa undang-undang ini telah menyebabkan pelanggaran Hak Asasi Manusia. Melihat pandangan yang terpecah seperti ini, pemerintah pusat dan Aceh disarankan untuk mengambil tindakan lebih lanjut untuk menghindari kebingungan masyarakat Aceh dan konflik agama di masa depan.Kata kunci: Hukum Syariah, Aceh, Non-Muslim